The Attitudes toward Pre-Exposure Prophylaxis (PrEP) Scale: Development and validation. Issue 2 (3rd April 2019) - Jaspal, Rusi; Lopes, Bárbara; Maatouk, Ismael
Abstract: Pre-exposure prophylaxis (PrEP) is a novel, clinically effective biomedical HIV prevention tool but it has not met with widespread public acceptance. In this article, the results of a study designed to develop a scale for measuring attitudes toward PrEP is presented. The psychometric properties of the scale are described for use in both the general population and in-patient samples. Two hundred twenty-two university students completed the Attitudes toward PrEP Scale (APS) and additional measures of attitudes toward gay men, Black Africans, and condom use. The APS comprised three factors (Attitudes toward the Science of PrEP, Perception of Sexual Health Risks of PrEP, and Perception of Dangerous Effects of PrEP), which explained 49.31% of the variance. The 14-item APS had a good internal consistency, α = .72, and satisfactory concurrent validity with measures of condom use, and attitudes toward social groups associated with PrEP. Additional studies in other nonstudent samples are required to assess the external validity of the scale.